2022
DOI: 10.3791/63988
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Multicue Cellular Microenvironments by UV-Photopatterning of Three-Dimensional Cell Culture Substrates

Abstract: The extracellular matrix is an important regulator of cell function. Environmental cues existing in the cellular microenvironment, such as ligand distribution and tissue geometry, have been increasingly shown to play critical roles in governing cell phenotype and behavior. However, these environmental cues and their effects on cells are often studied separately using in vitro platforms that isolate individual cues, a strategy that heavily oversimplifies the complex in vivo situation of multiple cues.Engineerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Integrating this basis with recent breakthroughs in tissue fabrication, biophysics, and biomaterials, should enable bottom-up strategies for the design of bioreactors that are well-suited to investigate the mechanobiology of HP and OS. Novel methods in 3D tissue bioprinting [159][160][161][162][163], mechanical characterization of biological tissues [164][165][166][167][168][169], the formulation of responsive biomaterials with tunable biomechanical and biochemical properties [170][171][172][173][174][175][176], and the development of 3D organotypic cell cultures [177][178][179][180][181][182] highlight a battery of innovations that can be exploited towards the design of advanced materials systems and bioreactors for the control of HP and OS.…”
Section: Conventional and Advanced Bioreactors For 3d Mechanobiologic...mentioning
confidence: 99%
“…Integrating this basis with recent breakthroughs in tissue fabrication, biophysics, and biomaterials, should enable bottom-up strategies for the design of bioreactors that are well-suited to investigate the mechanobiology of HP and OS. Novel methods in 3D tissue bioprinting [159][160][161][162][163], mechanical characterization of biological tissues [164][165][166][167][168][169], the formulation of responsive biomaterials with tunable biomechanical and biochemical properties [170][171][172][173][174][175][176], and the development of 3D organotypic cell cultures [177][178][179][180][181][182] highlight a battery of innovations that can be exploited towards the design of advanced materials systems and bioreactors for the control of HP and OS.…”
Section: Conventional and Advanced Bioreactors For 3d Mechanobiologic...mentioning
confidence: 99%
“…Studies showed that cell attachment of primary human keratocytes and human dermal fibroblasts could be influenced by these protein contact-guidance cues but also geometrical cues such as the substrate curvature. The reported photopatterning technique in combination with digital masks enabled the formation of various geometries with a resolution as small as 1.5 μm . Recently, Falandt and colleagues reported the use of volumetric bioprinting to draw and imprint gradients and patterns of growth factors in any custom-designed geometry across a centimeter-scale …”
Section: Hydrogel Patterning By Means Of Photodegradation Photorelaxa...mentioning
confidence: 99%
“…The reported photopatterning technique in combination with digital masks enabled the formation of various geometries with a resolution as small as 1.5 μm. 125 Recently, Falandt and colleagues reported the use of volumetric bioprinting to draw and imprint gradients and patterns of growth factors in any custom-designed geometry across a centimeter-scale. 126 In conclusion, light-triggered methods are very interesting for the local modification of photoresponsive hydrogels as it can be delivered with very high precision and thus good resolution.…”
Section: Hydrogel Patterning By Means Of Photodegradation Photorelaxa...mentioning
confidence: 99%